Three new species of Oleandra (Oleandraceae, Polypodiopsida) from the Neotropics, and notes on the morphological groups among the Neotropical species - Miranda, Cecília V.; Schwartsburd, Pedro B.; Labiak, Paulo H.; Prado, Jefferson [UNESP] (Springer Nature, 2021)
Three new species of Oleandra from the Neotropics are described, illustrated, and compared to similar species. Oleandra amazonica and O. steyermarkii are endemic to the Guiana Shield, whereas O. hovenkampii has an apparent disjunct distribution, being known from Peru and Costa Rica. We also re-define the informal, morphological groups of Neotropical Oleandra: 1. Species with slender, creeping stems clothed with squarrose, spreading scales, and forming stipe-like phyllopodia, with alternate and spaced phyllotaxy; 2. An intermediate group between groups 1 and 3, composed of species with mostly slender, creeping stems clothed with appressed scales, and forming stipe-like phyllopodia, with mixed phylotaxy (alternate in some species, tending to verticilate in others); and 3. Species with stout, climbing to ascending stems clothed with appressed scales, and forming stem-like phyllopodia, with verticillate phyllotaxy. In total, we recognize 21 valid species for the Neotropics, and tentatively accommodate them in those three groups, each one with 9, 5, and 7 species, respectively.
Keywords: Amazon; biodiversity; endemism; ferns; high elevations; Mount Roraima